2018
DOI: 10.1159/000492518
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Peptide Improves Diet-Induced Hepatic Fat Deposition and Hepatocyte Proinflammatory Response in SAMP8 Ageing Mice

Abstract: Background/Aims: High-fat diet (HFD)-induced nonalcoholic fatty liver disease (NAFLD) poses therapeutic challenges in elderly subjects. Due to lack of efficient drug therapy, plant-based bioactive peptides have been studied as alternative strategy in NAFLD and for less toxicity in elderly. To mimic fatty liver in aging conditions, researchers highly commended the genetically engineered strains SAMP8 (senescence-accelerated mice prone 8). However, there is a paucity of reports about the anti-steatosis effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…To assess the in vivo effects of the casein-derived peptides, we established the HCD-induced hyperlipidemic mouse model and orally administered peptide 9 or 12 at a concentration of 10 mg/kg to the mice five times a week following the previous study [ 33 ]. Peptide treatment was begun concurrently with HCD administration to investigate both its prophylactic and therapeutic effects.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the in vivo effects of the casein-derived peptides, we established the HCD-induced hyperlipidemic mouse model and orally administered peptide 9 or 12 at a concentration of 10 mg/kg to the mice five times a week following the previous study [ 33 ]. Peptide treatment was begun concurrently with HCD administration to investigate both its prophylactic and therapeutic effects.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above‐mentioned bioactivities, patatin or patatin‐derived peptides have been reported to show other physiological activities, such as anti‐inflammatory, anticancer, glucose uptake stimulating and neuropeptide inhibitory activities (Sun et al ., ; Fu et al ., ; Dumeus et al ., ). Patatin can display antiproliferative activities towards mouse melanoma B16 cells in a dose‐dependent manner (Sun et al ., ) by inducing cell cycle arrest in the G1 phase and cell apoptosis, which was further verified by flow cytometry.…”
Section: Beneficial Effects Of Patatin On Health and Food Applicationmentioning
confidence: 97%
“…A recent study by Dumeus et al . () has reported that a decapeptide (DIKTNKPVIF) from patatin is capable of ameliorating liver steatosis in high fat diet‐fed SAMP8 mice via activating hepatic adenosine 5′‐monophosphate (AMP)‐activated protein kinase signalling and attenuating protein expression of proinflammatory mediators via mitogen‐activated protein kinase signalling pathway.…”
Section: Beneficial Effects Of Patatin On Health and Food Applicationmentioning
confidence: 99%
“…After being stimulated, JNK accumulates in the nucleus and causes the corresponding gene (IL-1 and TNF- α ) expression, resulting in inflammatory response ( Figure 2 ) [ 44 ]. Various food protein-derived BAPs can inhibit inflammation via this MAPK pathway, such as DEDTQAMPFR, DEDTQAMPF [ 18 ], FLV [ 20 ], MLGATSL, MSYSAGF [ 18 ], β -Ala-His [ 35 ], pyroGlu-Leu [ 36 ], DIKTNKPVIF [ 45 ], VPP [ 46 ], WH [ 41 ], γ -EC, and γ -EV [ 47 ].…”
Section: Pathways Involved In the Inhibition Of Chronic Intestinalmentioning
confidence: 99%
“…Numbers of BAPs derived from various food proteins (milk, plant, egg, soybean, meat, wheat, rice, potato, corn silk, fish, etc.) have been found to be well suited to treat inflammation or IBD symptoms in vivo ( Table 2 ), such as Ala-Gln (AQ) [ 9 , 52 54 ], DIKTNKPVIF [ 45 ], EWP [ 55 ], GLTSK [ 56 ], glycomacropeptide [ 57 60 ], lunasin [ 15 ], IRW [ 11 , 61 63 ], IQW [ 62 64 ], KGHYAERVG [ 65 ], KPV [ 66 ], PTGADY [ 67 ], QCQCAVEGGL [ 68 ], QEPVL, QEPV [ 6 ], RILSILRHQNLLKELQDLAL [ 69 ], SSEDIKE [ 70 ], TMKLLLVTL [ 43 ], VPP [ 31 , 46 , 71 , 72 ], IPP [ 71 , 72 ], VPY [ 33 ], WH [ 41 ], casein hydrolysates [ 73 ], soybean dipeptides and tripeptides [ 74 ], peptide P-317 [ 75 ], pyroGlu-Leu [ 76 ], β -Casofensin [ 77 ], γ -EC, and γ -EV [ 47 ]. These studies suggest that oral administration of food-derived BAPs have anti-inflammatory effects, and they can be the therapeutic agents for inflammatory-related diseases, including IBD [ 78 ].…”
Section: The In Vivo Studies Of Baps On Inflammmentioning
confidence: 99%